Student Experience, Career Influence, and Supply Chain Competitions:#xd; A Mixed-Method Analysis of Students, Judges, and Alumni. Issue 4 (2nd October 2022) - Lynch, Daniel; Arguea, Nestor; LeMay, Stephen A.; Keller, Scott; Kimball, Bob
ABSTRACT: Students often identify specific moments or specific individuals who changed the courses of their academic experience, choices of careers, or the paths of their careers. Business schools have attempted to frame these moments and experiences in the form of high-impact practices (HIP). This research examines a live case competition with business professionals as judges. We have incorporated survey results from student participants, comments from competition judges, and interviews with former participants. The former participants explain how this competition affected their careers and educational experiences. We incorporate the perceptions of students, industry judges, and former participants to give a unique view of this HIP. We also blend empirical analysis, using qualitative and quantitative methods. The research contributes to the marketing education literature in unusual if not unique ways because of the interviews with former participants who have advanced in their careers. This research also underscores the idea that live case competitions of this nature have substantial impacts on students' academic experiences and their careers, so such case competitions have earned the designation of High Impact Practice.